An African Interpretation of Paulâ€™s Understanding of The Holy Spirit - Ejenobo, David T. (European Scientific Journal, ESJ, 2016)
The doctrine of the trinity has generated a lot of controversies down the centuries among New Testament scholars. The problem generated by scholars to dissect the Personhood of God has resulted in various shades of interpretations on the relationship between God the Father, the Son and the Holy Spirit. It is against this background that this paper seeks to examine Paulâ€™s understanding of the Holy Spirit viewed against the backdrop of the doctrine of the Trinity. This study adopted the textual critical method to examine the various nuances of Paulâ€™s allusion to the Holy Spirit with a view to situating them within a proper understanding of the concept of the trinity. The author discovered that for Paul there is no personality distinction between God the Father, the Son and the Holy Spirit, since man encounters these â€œpersonsâ€ in the spiritual realm. Applying the hermeneutical method of contextual interpretation, the author is of the opinion that for the African, conceptualizing God within the realm of the Spirithood of God would be a more practical way of describing the activities of God the Father, the Son and the Holy Spirit than the Western conceptualization of the Three Persons in on Godhead.